EVALUASI AKSESIBILITAS WEBSITE COVID19.KALTIMPROV.GO.ID MENGGUNAKAN SORTSITE 5.3.5 - Bambang Irawan; Muhammad Nizar Hidayat (Jurnal Paradigma (JP), 2020)
This article aims to evaluate the accessibility of a government website, covid19.kaltimprov.go.id which created for disseminating the official information regarding the spread of covid-19 in East Kalimantan. Accessibility is an important aspect of a website because it indicates how far the range of information dissemination of such website. In this article we use SortSite 5.3.5, an online website testing software. The result shows that accessibility of covid19.kaltimprov.go.id still score below average with so many pages with accessibility issues. It is therefore need attention from East Kalimantan government to improve the accessibility level of their website.Keywords: Accessibility, Website, Covid-19, East Kalimantan